The Influence of Collaboration of Discovery Learning and ARIAS on Students' Critical Thinking Abilities (Universitas Negeri Semarang, 2019)
The purpose of the study was to analyze the influence of discovery learning model, ARIAS model, and the collaboration of the discovery learning and ARIAS model on the critical thinking ability of the fifth-grade elementary school students. This study applied a quantitative method in the form of quasi-experimental design using pre-test and post-test scores. The samples in this study were taken by using purposive sampling technique. There were three elementary schools participated in this study, and they were the fifth-grade students at Public Elementary School Kebonagung 2, the fifth-grade students at Public Elementary School Kebonagung 3 and the fifth-grade students at Public Elementary School Prigi 2. The data collection techniques used were descriptive test questions. The results showed that there was an influence of discovery learning model, ARIAS, and the collaboration of the discovery learning and ARIAS model on the critical thinking ability of students. The average value of students' critical thinking skills tests using discovery learning models = 79.38 (good category). The average value of the students' critical thinking skills test on the implementation of the ARIAS model = 85.12 (good category). The average value of the application of the collaboration of discovery learning and ARIAS model = 89.03, included in the excellent category.